Updated chronology for the Miocene hominoid radiation in Western Eurasia - Casanovas-Vilar, Isaac (National Academy of Sciences, 2011)
Extant apes (Primates: Hominoidea) are the relics of a group that was much more diverse in the past. They originated in Africa around the Oligocene/Miocene boundary, but by the beginning of the Middle Miocene they expanded their range into Eurasia, where they experienced a far-reaching evolutionary radiation. A Eurasian origin of the great ape and human clade (Hominidae) has been favored by several authors, but the assessment of this hypothesis has been hampered by the lack of accurate datings for many Western Eurasian hominoids. Here we provide an updated chronology that incorporates recently discovered Iberian taxa and further reevaluates the age of many previously known sites on the basis of local biostratigraphic scales and magnetostratigraphic data. Our results show that identifiable Eurasian kenyapithecins (Griphopithecus and Kenyapithecus) are much younger than previously thought (ca. 14 Ma instead of 16 Ma), which casts serious doubts on the attribution of the hominoid tooth from Engelswies (16.3–16.5 Ma) to cf. Griphopithecus. This evidence is further consistent with an alternative scenario, according to which the Eurasian pongines and African hominines might have independently evolved in their respective continents from similar kenyapithecin ancestors, resulting from an early Middle Miocene intercontinental range extension followed by vicariance. This hypothesis, which would imply an independent origin of orthogrady in pongines and hominines, deserves further testing by accurately inferring the phylogenetic position of European dryopithecins, which might be stem pongines rather than stem hominines.